PROPUESTA DE RUTA TURÍSTICA DE LA PARROQUIA SAN ANDRÉS, CANTÓN CHINCHIPE, PROVINCIA DE ZAMORA CHINCHIPE - Cabrera Álvarez, Luz Victoria (2018)
The parish of San Andrés has a great natural wealth that is not being properly valued and used in the tourist field, however the tourist activity is not carried out in the best conditions, so it has been necessary to work with the main actors involved in the field of tourism with the purpose of upgrading the existing tourist sites and services, as well as to generate new tourism proposals, offering better opportunities for economic development, complementing the agricultural, livestock and commercial activity of the sector, in order to improve tourism taking into account the existence of the natural attractions that the parish has. This project aims to promote and promote greater attention and importance to tourism, which in the future will be reflected in the increased increase in visitors, consequently in boosting the local economy. According to these antecedents the work was developed based on the approach of the following: General Objective; Elaborate the tourist route of the San Andrés parish, Chinchipe Canton, Zamora Chinchipe Province, as well as its development. Specific Objectives: First Objective; Make a diagnosis of the main tourist attractions of the San Andrés parish, Canton Chinchipe, Province of Zamora Chinchipe. For the fulfillment of this objective, techniques such as direct observation and interviews with actors involved in the tourism activity were presented, the situational tourism diagnosis was made through the synthetic method, through the matrix of Carla Ricaurte Quijano, inventory and hierarchy sheets of tourist attractions of the Ministry of Tourism (MINTUR) for the identification and ranking of the natural and cultural tourist attractions that the parish possesses, likewise the influence on the project was prioritized through the SWOT matrix. Second Objective; Design the tourist route for the San Andrés parish, Canton Chinchipe, Province of Zamora Chinchipe. For the elaboration of the present objective, we used the technique of direct observation and field work in which the georeferencing of the GPS points was established to make the elevation of coordinates such as altitude, latitude, distances and exact time of the route, which were later traced on the tourist route, using attractive pictograms, activities and tourist support services. In addition, the brand was designed identifying the most representative of the parish and then the name of the route called "Natural Tourist Route of the Cascades" was also considered. The itinerary and the script were also elaborated, continuing the established order of the same. Third Goal; Propose promotion strategies for the tourist route of the San Andrés parish, Chinchipe Canton, Zamora Chinchipe Province. For the development of the following objective the following was considered; Product strategies were established to publicize the tourism product through advertising media: such as social networks Facebook and instagram, a billboard, leaflets, souvenirs (t-shirts, caps, tomatodos and ecological 5 backpacks). With the development of the aforementioned SWOT matrix, it was possible to identify the strengths, opportunities, weaknesses, and threats. Strategies for tourism promotion were proposed with the help of the interviews carried out with the entities involved; for this, field work was necessary, direct observation, once the information was collected, the SWOT crossing was made, which determined the strategies proposed in the present work. This research work required the use of methods, such as the analytical, to review the available material, synthetic used to order and build what was researched, the inductive allowed to study the features and characteristics of each site in order to establish their social impact and economic for the sector, and with this to be able to propose possible strategies of tourist development, and the deductive through which the respective conclusions and recommendations could be elaborated. Other techniques used were observation to make a quick survey of the current reality of the parish; the interview that allowed to sustain the design of the thesis proposal with the actors involved. This investigation in its final part, the conclusions and recommendations are presented emphasizing the importance and the total support from the municipal and parochial GADs to promote this proposal with tourist aims; allowing to determine that the parish of San Andrés has natural and cultural attractions of great importance, which need to be promoted and disseminated for the development of tourism. It is also recommended that the Gobierno Autónomo Descentralizado Parroquial de San Andrés should be the promoter of tourism initiatives, dissemination and promotion of tourism.